Creative Visualization of Marine Life through 3D Animation as a Communication Medium for Preservation: A Case Study of Pulau Payar Marine Park, Malaysia - Zairun, Roslan; Anuar, Ayob; Aslina, Mohd Jainal (IP Media Sdn. Bhd. & SiMo Press Sdn. Bhd., 2026)
This research about creative visualization of marine life using Three-Dimensional (3D) animation as a communication medium to enhance awareness, understanding, and immersive experience of marine ecosystems, focusing on Pulau Payar Marine Park, Malaysia. Data were collected through participant observation (underwater photography and video) and expert interviews in marine biology, conservation, underwater photography, and 3D animation. Thematic analysis identified key patterns, including the diversity of tropical species such as soft corals, hard corals, and ornamental fish, and their integration into the animation development process. The animation pipeline included field data collection, 3D modeling, texturing, rigging, rendering, and final animation, producing realistic visual representations aligned with scientific data. Findings show that 3D animation effectively conveys complex information in an engaging, interactive, and understandable way. While challenges remain regarding cost, time, and audience accessibility, exploring future technologies such as AR, VR, and MR can further enrich educational experiences and support marine biodiversity conservation.